The Landscape of Emotions in Virtual Communication: A Multimodal Analysis of Metaverse Interactions - Febriana, Erika (PT. Anagata Sembagi Education, 2025)
The development of the metaverse as an immersive virtual space has changed the pattern of human communication by presenting multimodal interactions involving verbal, non-verbal, and digital environmental aspects, this study aims to analyze the emotional landscape in virtual communication in the metaverse through a multimodal approach with the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. From the results of the review of 25 selected articles, it was found that non-verbal avatar expressions, such as gestures and digital facial expressions, have a dominant contribution to the perception of emotions, while verbal communication plays a limited role and the virtual environment functions as a modulator of emotional experience, the integration of these three modalities results in more authentic emotional experiences, increases empathy, and strengthens social involvement in digital interactions. This research provides practical implications for more realistic avatar design, the development of interactive virtual environments, and the application of multimodal approaches to improve the quality of communication and psychological well-being of users in the metaverse.